2019
DOI: 10.1002/cam4.2494
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA PART1 promotes progression of non‐small cell lung cancer cells via JAK‐STAT signaling pathway

Abstract: Non‐small cell lung cancer (NSCLC), the major type of lung cancer, becomes the greatest threat to the life of people. Growing evidence shows prostate androgen‐regulated transcript 1 (PART1) is considered as effective markers for prostate cancer, and has been shown to be associated with poor prognosis of NSCLC. However, the tumorigenic mechanism of PART1 in NSCLC remains to be investigated. In this study, we found that the expression of PART1 was robustly induced in NSCLC tissues and cell lines. Functional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 48 publications
5
40
0
Order By: Relevance
“…Sustained activation of JAK/STAT signaling has been demonstrated in tumor initiation, progression, and cancer stem cell (CSC) maintenance in several human cancers. For instance, Zhu et al (2019) reported that long non-coding RNA PART1 enhanced the proliferation, migration, and invasion via activation of JAK-STAT signaling in non-small-cell lung cancer cells. Dolatabadi et al (2019) demonstrated that the activation of JAK-STAT signaling regulates the CSC properties in myxoid liposarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained activation of JAK/STAT signaling has been demonstrated in tumor initiation, progression, and cancer stem cell (CSC) maintenance in several human cancers. For instance, Zhu et al (2019) reported that long non-coding RNA PART1 enhanced the proliferation, migration, and invasion via activation of JAK-STAT signaling in non-small-cell lung cancer cells. Dolatabadi et al (2019) demonstrated that the activation of JAK-STAT signaling regulates the CSC properties in myxoid liposarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 39 directly regulated lncRNAs, previous studies indicated that lncPART1 and lncMIR17HG are associated to tumorigenesis 42‐47 . Besides, lncPART1 and lncMIR17HG demonstrated significant differential expression in ME‐180/shp63 cells.…”
Section: Resultsmentioning
confidence: 94%
“…This indicated that lncRNA PART1 is overexpressed in NSCLC cell lines, corroborating previous studies. 22,23 We then investigated if modulating PART1 expression will alter chemosensitivity of BEAS-2B or the NSCLC cell lines. PART1 was overexpressed in BEAS-2B cells, whereas the NSCLC cells lines were transfected with PART1 siRNA.…”
Section: Resultsmentioning
confidence: 99%
“…21,25,26 PART1 has been indicated previously in glioblastoma, 27 esophageal squamous cell carcinoma (ESCC), 28 oral cancer, 29 colorectal cancer, 30 as well as in survival and disease progression of NSCLC. 22,23 However, there has been no previous study elucidating a role of PART1 in chemoresistance to erlotinib in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation